2015
DOI: 10.1016/j.ijheatmasstransfer.2015.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Modeling average gas–solid heat transfer using particle-resolved direct numerical simulation

Abstract: Particle-resolved direct numerical simulation Average fluid temperature equation Two-fluid model Fixed assembly of particles Nusselt number correlation for gas-solid flow a b s t r a c tThe purpose of this work is to develop gas-solid heat transfer models using Particle-resolved Direct Numerical Simulations (PR-DNS). Gas-solid heat transfer in steady flow through a homogeneous fixed assembly of monodisperse spherical particles is simulated using the Particle-resolved Uncontaminated-fluid Reconcilable Immersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 49 publications
(110 reference statements)
5
66
0
Order By: Relevance
“…The comparison shows that our methodology is fully capable of reproducing the results of Deen et al [33] and Sun et al [32], which are given in terms of an average, and not particle-based, Nusselt number. Discrepancies are observed for (i) high values of Nu (which are, however, outside the range of validity of correlation denoted as Nu DS ), and (ii) for ρ = 2 (see Figure 10a).…”
Section: Benchmarks For the Nusselt Number Predictionmentioning
confidence: 55%
See 2 more Smart Citations
“…The comparison shows that our methodology is fully capable of reproducing the results of Deen et al [33] and Sun et al [32], which are given in terms of an average, and not particle-based, Nusselt number. Discrepancies are observed for (i) high values of Nu (which are, however, outside the range of validity of correlation denoted as Nu DS ), and (ii) for ρ = 2 (see Figure 10a).…”
Section: Benchmarks For the Nusselt Number Predictionmentioning
confidence: 55%
“…The use of an immersed boundary approach allows to solve the governing equations in a global domain Ω with simple shape (which can be efficiently meshed using a simple Cartesian grid) rather than the highly complex fluid domain Ω f . This is why immersed boundary methods are frequently used in the field of suspension flows, even in case particles are arrested (see, for example in [8] or [32,33,34,35,36,37]). The HFD-IB approach ensures that no errors arise due to highly skewed cells and, most important, it eliminates the effort to build a body-fitted mesh.…”
Section: Mesh Generation and Cfd Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models to define intraparticle diffusion [35,38] are given in Equations (3)- (5), while the [18,21,42,43] versus porosity value inside the particle. The comparison is made to Nusselt number from the ideal external heat transfer case without inside particle mesh.…”
Section: D Packed Bed Modelmentioning
confidence: 99%
“…The detailed analysis of the particle proximity effects is beyond the scope of the present work and requires the use of stochastic procedures, because of the fast dynamics of suspended particle arrangements and broad size distributions of suspended polymer particles. [39][40][41][42][43][44][45][46][47][48][49] Previous studies analyzed effects of particle clustering in polymerization media using CFD, [ 10,[24][25][26][27] using some fi xed particle confi gurations to represent the system, which does not seem appropriate for analysis of suspended particles in the pneumatic section of the MZCR reactor. In general, these studies showed that particle clustering can lead to worse heat transfer conditions and to particle temperature rise.…”
Section: Introductionmentioning
confidence: 99%